Amplification of factors of regional markets transformations in the context of generation theory - R. S. Blizkiy; E. A. Divaeva (Вестник университета, 2023)
The article summarizes scientific ideas about essence of Russian regions and regional markets as actively transforming systems of economic relations in complex geopolitical and socio-economic conditions. The authors propose a process-role model of Russian regional markets functioning, consider relationship and dependence of median number and age structure of the country’s population, highlight the dominant problem of aging and decline in the number of able-bodied population. The researchers propose to consider combinatorics of the generations theory factors within the framework of Russian regional markets development. The research achievement consists in theoretical and methodological provisions development justifying amplification of market development factors considering different archetypes of consumer generations, consumer triggers presented, as well as regulatory aspects of regional policy aimed at strengthening the all-Russian civil identity and social stability in society. Methods of scientific research: system analysis, synthesis, economic and statistical method, methods of abstraction and inductive logic. The purpose of the study is to determine the content of regional markets meaning on the basis of the analysis of Russian regional markets regularities of transformations and corresponding regional specifics, to develop a process-role model considering existing paradigms of regional economy, realizing the dilemma of contradictions of consumers generations, business and state in the demands, values, and space of the market, entailing causal relationship of amplification of Russian markets transformation factors. The scope of application of the results obtained is multifaceted – from market infrastructure organizations to state structures. The latter will find the results useful in implementing state programs.